2015
DOI: 10.1002/clc.22481
|View full text |Cite
|
Sign up to set email alerts
|

Exercise and Physical Activity for the Post–Aortic Dissection Patient: The Clinician's Conundrum

Abstract: Despite the paucity of evidence, it is often presumed, and is physiologically plausible, that sudden, acute elevations in blood pressure may transiently increase the risk of recurrent aortic dissection (AD) or rupture in patients with a prior AD, because a post‐dissection aorta is almost invariably dilated and may thus experience greater associated wall stress as compared with a nondilated aorta. Few data are available regarding the specific types and intensities of exercise that may be both safe and beneficia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
62
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(64 citation statements)
references
References 28 publications
0
62
2
Order By: Relevance
“…In our clinical practice, we encountered patients with conservatively treated aortic dissection who became aware of reduced physical strength as the degree of bed rest became less strict, and became depressive due to anxiety about economic issues or return to work [19]. Patients with aortic dissection require bed rest, but a severe restriction of physical activity may decrease the patient's physical function and quality of life [20]. Muscle fiber type changes in response to an exercise environment [21], and a study has reported that resistance exercise three times a week counteracted the atrophy of lumbar muscle even in patients on bed rest [22].…”
Section: Discussionmentioning
confidence: 99%
“…In our clinical practice, we encountered patients with conservatively treated aortic dissection who became aware of reduced physical strength as the degree of bed rest became less strict, and became depressive due to anxiety about economic issues or return to work [19]. Patients with aortic dissection require bed rest, but a severe restriction of physical activity may decrease the patient's physical function and quality of life [20]. Muscle fiber type changes in response to an exercise environment [21], and a study has reported that resistance exercise three times a week counteracted the atrophy of lumbar muscle even in patients on bed rest [22].…”
Section: Discussionmentioning
confidence: 99%
“…This is true of all patients who survive an acute AD; however, very little is known about postoperative exercise limits, and given that moderate exercise is important to maintain good heart health and limit future risks, clinicians have to find a balance when providing advice. Recommendations for activities of 3–5 Metabolic Equivalent of Tasks (METS) for at least 30 min on most days and avoidance of any lifting, which leads to straining, have been made4; however, a survey of clinicians found great variability on the BP and HR limits that they recommend to their patients 5…”
Section: Outcome and Follow-upmentioning
confidence: 99%
“…In contrast, heavy weight lifting, which may transiently evoke excessive increases in SBP (>300 mm Hg) ( 10 -13 ), has been suggested as the trigger for AD in numerous reports ( 14 -16 ). Consequently, it seems reasonable for post-AD patients to avoid strenuous weightlifting performed to failure or lifting heavy objects to decrease the risk for future aortic dilation, dissection, and/or aortic rupture ( 6 ). For individuals with known aortic dilation, it appears that lifting up to 50% of their body weight during the bench press or an equivalent level of perceived exertion for other strength exercises is relatively safe, provided that the peak SBP remains below 200 mm Hg ( 8 , 16 ).…”
Section: Invited Commentarymentioning
confidence: 99%
“…Because structured aerobic exercise lowers the product of the heart rate (HR) and SBP at rest and at any given level of submaximal exercise, signifying a reduction in the rate-pressure product, a key determinant of myocardial oxygen consumption (r = 0.92) ( 17 , 18 ), it is feasible that exercise regimens might lower lifelong recurrent aortic risk during exertion-related and nonexertion (e.g., emotional) stresses. Since β-blockers are associated with improved survival in patients with prior AD, presumably by reducing HR, myocardial contractility, and abrupt increases in ventricular pressure ( 9 ), it is plausible that regular exercise may also serve as a cardioprotective intervention for the AD patient ( 6 ). Moreover, the associated increase in cardiorespiratory fi tness has also been shown to be a strong prognostic indicator, inversely related to cardiovascular and allcause mortality in patients with and without heart disease ( 19 ).…”
Section: Invited Commentarymentioning
confidence: 99%